2008
DOI: 10.1002/chem.200701981
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Properties, and Redox Behavior of Mono‐, Bis‐, and Tris[1,1,4,4,‐tetracyano‐2‐(1‐azulenyl)‐3‐butadienyl] Chromophores Binding with Benzene and Thiophene Cores

Abstract: Mono-, bis-, tris-, and tetrakis(1-azulenylethynyl)benzene and mono- and bis(1-azulenylethynyl)thiophene derivatives 5-10 have been prepared by Pd-catalyzed alkynylation of ethynyl arenes with 1-iodoazulene derivative or the 1-ethynylazulene derivative with tetraiodobenzene and iodothiophenes under Sonogashira-Hagihara conditions. Compounds 5-10 reacted with tetracyanoethylene in a [2+2] cycloaddition reaction to afford the corresponding 1,1,4,4,-tetracyano-2-(5-isopropyl-3-methoxycarbonyl-1-azulenyl)-3-butadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 126 publications
(94 citation statements)
references
References 33 publications
1
91
0
2
Order By: Relevance
“…Likewise, treatment of 4 with TCNE afforded 10 in 88 % yield, along with 14 [5] in 5 % yield (Scheme 3). The resulting mono adduct 10 was treated with TCNQ to give the TCNE/ TCNQ double adduct 12, with a thiophene core, in 85 % yield.…”
Section: Synthesismentioning
confidence: 96%
See 3 more Smart Citations
“…Likewise, treatment of 4 with TCNE afforded 10 in 88 % yield, along with 14 [5] in 5 % yield (Scheme 3). The resulting mono adduct 10 was treated with TCNQ to give the TCNE/ TCNQ double adduct 12, with a thiophene core, in 85 % yield.…”
Section: Synthesismentioning
confidence: 96%
“…Treatment of 3 with TCNE gave the mono adduct 9 in 88 % yield, along with 13 [5] in 4 % yield (Scheme 3). [7] The synthesis of the TCNE/TCNQ double adduct 11 was achieved in 84 % yield by treatment of 9 with TCNQ (Scheme 3).…”
Section: Synthesismentioning
confidence: 96%
See 2 more Smart Citations
“…[22] In the case of azulene derivatives, we have also reported that 1,1,4,4-tetracyano-2,3-bis[5-isopropyl-3-(methoxycarbonyl)-1-azulenyl]butadiene showed solvatochromism. [23] We examined the solvatochromic effect of 12 in eight solvents, and the solvent dependence of the absorpwww.eurjoc.org Figure 4. ORTEP drawing of the molecular structure of 13.…”
Section: Resultsmentioning
confidence: 99%